Pemaknaan ajaran paramita pada relief Jatakamala di Candi Borobudur: Perspektif semiotika - So Tju Shinta Lee; Agus Aris Munandar (Berkala Arkeologi, 2022)
This paper examines how the Jatakamala reliefs at Candi Borobudur represent the teachings of six perfections (sat-paramita), the social roles of the main characters, and the universal values in the stories. This research is necessary as previous studies do not provide adequate analyses on how Jatakamala is associated with the practice of perfections. By integrating three data components: the reliefs, the manuscript, and the sutras on six perfections, this study employed pragmatic semiotics by Charles Sanders Peirce to identify the perfection(s) in five Jatakamala stories. Thematic analysis was employed to discern social roles and universal messages in 14 stories. Application of Peirce's triadic shows that each story represents multiple perfections. The main characters in Jatakamala play an active social role and tackle issues in society through actions and exemplification. Jatakamala also contains universal values as a means for learning and education.